2013
DOI: 10.2140/ant.2013.7.733
|View full text |Cite
|
Sign up to set email alerts
|

F-blowups of normal surface singularities

Abstract: Abstract. We study F-blowups of non-F-regular normal surface singularities. Especially the cases of rational double points and simple elliptic singularities are treated in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…We divide the proof into two cases, according to whether E is ordinary or supersingular. First we recall the following: Lemma 5.4 ( [A], [HSY,Lemma 4.12]). Let E be an elliptic curve in characteristic p and let q = p e for e ≥ 0.…”
Section: Proofmentioning
confidence: 99%
“…We divide the proof into two cases, according to whether E is ordinary or supersingular. First we recall the following: Lemma 5.4 ( [A], [HSY,Lemma 4.12]). Let E be an elliptic curve in characteristic p and let q = p e for e ≥ 0.…”
Section: Proofmentioning
confidence: 99%
“…The main novelty in Villamayor's construction is that he showed that there exists a module E 1 of projective dimension at most 1 having rank e whose Fitting ideal F e (E 1 ) is a representative of [[E]] R , as a fractional ideal. This Fitting ideal F e (E 1 ) is in fact a sub-determinantal ideal of any matrix representing E, which gives an effective method to compute the blow up of R at E. For instance, N. Hara, T. Sawada and T. Yasuda have recently used this approach in [5] in order to compute explicitly F -blowups for some surface singularities by using Macaulay2 [10].…”
Section: Introductionmentioning
confidence: 99%